Justification of Safety of Homeopathic Medicines in a Registration Dossier - R. D. Subaev; G. N. Engalycheva; D. V. Goryachev (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2019)
Regulatory approaches to assessing the safety of homeopathic medicines in the Russian Federation and abroad are formed in accordance with regulatory acts, national and international rules and guidelines. Scientific literature is particularly important for justification of safety of homeopathic medicines. The purpose of this study was to determine the requirements and procedure for presenting justification of homeopathic medicines safety in the registration dossier in accordance with the documents of the Eurasian Economic Union and the European Union. According to the current Russian and foreign regulatory approaches the safety may be justified by scientific literature data on homeopathic use and by substantiation of the dosage in the case of medicines that have long experience of safe use and those that are authorized under a simplified procedure based on a dossier with a product instruction that does not establish indications for use. In both cases, there is no need to provide the results of preclinical or clinical studies of the drug. This approach reflects specific features of homeopathic medicines. An objective criterion of the safety of homeopathic medicines is the assessment of the dosage of active substances, taking into account the «first safe dilution» of homeopathic substances. A formal safety justification using registration data for similar drugs or additional information on the use of these pharmaceutical substances in homeopathy is also possible, but may be insufficient. The completeness and proper documentation of bibliographic data are the main criteria for an appropriate rationale for the safety of homeopathic products.